2002
DOI: 10.1104/pp.008201
|View full text |Cite
|
Sign up to set email alerts
|

Bundle Sheath Diffusive Resistance to CO2 and Effectiveness of C4 Photosynthesis and Refixation of Photorespired CO2 in a C4 Cycle Mutant and Wild-Type Amaranthus edulis  

Abstract: A mutant of the NAD-malic enzyme-type C(4) plant, Amaranthus edulis, which lacks phosphoenolpyruvate carboxylase (PEPC) in the mesophyll cells was studied. Analysis of CO(2) response curves of photosynthesis of the mutant, which has normal Kranz anatomy but lacks a functional C(4) cycle, provided a direct means of determining the liquid phase-diffusive resistance of atmospheric CO(2) to sites of ribulose 1,5-bisphosphate carboxylation inside bundle sheath (BS) chloroplasts (r(bs)) within intact plants. Compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 30 publications
4
71
4
Order By: Relevance
“…This upper limit for g bsc is less than oneseventh of the magnitude of g m in the MC (Table II). A study with A. edulis mutationally or chemically blocked in C 4 cycle function likewise showed conditionally higher rates of O 2 -dependent PSII linear electron transport (photorespiration) compared to controls and a similarly low conductance to CO 2 diffusion from the MC to sites of CO 2 fixation by Rubisco in the BSC (Kiirats et al, 2002). Furthermore, in this study J o at G is ,0.08 of the CO 2 -saturated J T (Table I).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…This upper limit for g bsc is less than oneseventh of the magnitude of g m in the MC (Table II). A study with A. edulis mutationally or chemically blocked in C 4 cycle function likewise showed conditionally higher rates of O 2 -dependent PSII linear electron transport (photorespiration) compared to controls and a similarly low conductance to CO 2 diffusion from the MC to sites of CO 2 fixation by Rubisco in the BSC (Kiirats et al, 2002). Furthermore, in this study J o at G is ,0.08 of the CO 2 -saturated J T (Table I).…”
Section: Discussionmentioning
confidence: 77%
“…A corresponding estimate of J o /J T at G in tobacco was at least 0.5 (Peterson 1989). Thus, photorespiration is indeed suppressed in C 4 relative to C 3 leaves due, in part, to the critical function of the BSC wall in restricting overcycling of CO 2 to the MC (Kiirats et al, 2002).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Leaf gas exchange characteristics, net rates of CO 2 fixation (A), C i , PPFD and leaf temperature were determined as by Laisk and Loreto (1996). Rubisco oxygenation rate (v o ), Rubisco carboxylation rate (v c ), and PS II electron transport (J O 2 ), were calculated from simultaneous measurements of leaf CO 2 exchange and fluorescence yield as in (Kiirats et al 2002).…”
Section: Plants and Growth Conditionsmentioning
confidence: 99%
“…Many studies have suggested that the enriched CO 2 leaves respond to atmospheric CO 2 enrichment to a greater extent than the ambient-CO 2 leaves as a result of increased quantum yields (Hanstein & Felle, 2002). A small increase in quantum yield may increase daily carbon gain under low light conditions (Kiirats et al, 2002). In our study, elevated CO 2 increased apparent quantum yields in the 800 and 1200 µmol mol -1 CO 2 treatments.…”
Section: Oil Palm Responses To Elevated Comentioning
confidence: 58%